Mengenal bahasa digital gen alpha: menelusuri dampak media sosial - Mustopa, Muhammad Rizki (Maliki Interdisciplinary Journal, 2025)
Generation Alpha, born after 2010, grows up amidst the development of digital technology, especially social media. This article examines the impact of social media on their language development, particularly in terms of vocabulary changes, communication styles, and the effects on formal language skills. While social media enriches vocabulary and enhances linguistic creativity, there is a risk of a decline in formal language abilities and the marginalization of the national language. The importance of education and family in maintaining a balance between language innovation and the preservation of linguistic values is the main focus. With the right approach, the influence of social media can enrich language without compromising national identity. Generation Alpha has great potential to be creative and responsible agents of change. With good guidance, they can create harmony between the dynamics of digital language and traditional linguistic values, ensuring that language not only develops but also remains relevant and meaningful in the future.